Antiproliferative effects of Trigonostemon xyphophyllorides on renal cell carcinoma via the PI3K/AKT pathway - Wang, Andong; Yang, Yuru; Chen, Tingting; He, Jinyan; Ling, Bai; Cheng, Xiaotian (Frontiers in Pharmacology, 2025)
BackgroundOne of the most well-known and deadly types of cancer is renal cell carcinoma (RCC). Not much research has been done on Trigonostemon xyphophyllorides (TX), an untested folk cure for cancer.MethodsUPLC-Q-TOF-MS/MS was used to systematically identify the components of TX. ACHN cell lines were used to assess TX’s pharmacological studies. Next, complexes with compound and gene will be included based on molecular docking and molecular dynamics simulations. In the end, signaling pathway analysis were used to elucidate the intricate mechanisms.ResultsAnalysis using UPLC-Q-TOF-MS/MS identified 47 major compounds in TX. In vitro experiments demonstrated that the TX extract was non-toxic to normal HK-2 cells but exhibited significant anti-proliferative effects on renal cancer ACHN cells, including inhibition of colony formation, suppression of cell migration, and anti-apoptotic properties. Transcriptomic analysis revealed that the anti-proliferative activity of TX was mediated through the PI3K-AKT signaling pathway. Subsequent validation was conducted using molecular docking, molecular dynamics simulation, qRT-PCR, and Western blotting techniques.ConclusionThis study utilized in vitro experimental validation techniques to establish that TX exerts its anti-proliferative effects by activating the PI3K-AKT signaling pathway. These findings elucidate the mechanism of TX action and provide a scientific basis for its prospective contemporary utilization.